Soil organic carbon balance across contrasting plant cover ecosystems in the Peruvian Amazon - Vallejos Torres, Geomar (2023)
The Peruvian Amazon has been significantly affected by land use and climate change, decreasing decomposition processes, which cause a significant depletion of soil C stocks. In this study, we estimated soil organic C (SOC) mediated by different plant covers in coffee (Coffea arabica L.) plantations and secondary forests in several districts of the San Martín Region, Peru. We calculated the critical threshold, saturation point, and the organic C deficit of these Amazonian soils. The association between geography, soil physical-chemical characteristics, and SOC was estimated through principal component analysis. Across all sites of the study, SOC stock had an average value of 69.19 t ha-1, with 48.95 t ha-1 constituting inorganic C. The highest SOC stock (225.28 t ha-1) was observed under secondary forest in the Jepelacio district. The SOC stocks were positively correlated with altitude and CaCO3 content only in secondary forests. The current measured amount of organic C within 15 cm soil depth was 28.5 g C kg-1, which is very low and close to the critical threshold (20.6 g C kg-1) -estimated based on its clay and silt contents. Our SOC stocks measurements indicated a worrisome situation, as they are close to the critical threshold, which exposes this area to a greater and stronger degradation.